Customer Relationship Management in Public Transportation: A Comparative Analysis - Mikhaylov, Andrey S.; Mikhaylova, Anna A. (International Review of Management and Marketing, 2016)
Customer complaint behaviour is an unlikely predictable sequence of actions and reactions a person goes through in case of a service failure. Yet a number of studies have raised the issue on the pattern of customer complaint behaviour and have even revealed some regularities on this matter. This article is dedicated to verify one of such patterns attributed to the public transportation services, while replicating the research methodology in a different contextual environment. We see how does the sequence of complainer's actions change based on the individual's perception of the cost of complaint, personal competences and the contextual resources that influence the complaint process. Research results have enabled to confirm the probability of a complaint reaction by categories, while the detailed pattern of customer complaint behaviour was partly confirmed. Keywords: service management, public transportation, service quality, customer complaint behaviour, behaviour pattern JEL Classifications: H42, L84, M310, R410